REAL-TIME KERNEL FUNCTION SYNTHESIS FOR SOFTWAREDEFINED RADIO AND PHASE-FREQUENCY MEASURING DIGITAL SYSTEMS - I. E. Tarasov; D. S. Potekhin (Российский технологический журнал)
This article presents a state-of-the-art method of mathematical analysis and implementation of a hardware-accelerated generator of kernel functions based on Morlet wavelet. The method is based on heavy usage of hardware cores of high-performance programmable logic devices (PLD) for generating harmonic and Gaussian modulating functions in real-time mode. The usage of modulated harmonic series allows tuning parameters of kernel functions both in frequency and time domains, while fine tuning of damping factor of Gaussian function is performed on the base of fixed-point representation of wavelet samples. The proposed hardware generator has a feature allowing to create high-order kernel functions, which is impossible with the approach based on storing coefficients in on-chip memory limited in size. An analysis performed in the article allows calculating a set of integration limits and corresponding damping coefficients for Gaussian modulating function. Implementation on the PLD was performed with combination of existing IP-cores based on CORDIC algorithm and original developed components. Modelling and implementation are performed with Kintex-7 series PLD. Using this approach several high-precision systems were designed. These systems are precision measurement devices for frequency and phase measurements. They also may be used for software-defined radio devices, including pure digital implementation of an input radio-frequency signal. Some examples are also reviewed.